SIMULASI SISTEM PENGHITUNG JUMLAH MOBIL KELUAR DAN PENGHITUNGAN TARIFNYA BERDASARKAN LAMA WAKTU PADA GEDUNG PARKIR MOBIL BERLANTAI TIGA BERBASIS MIKROKONTROLER ATMEGA 8535 - Ary M, Ruky Sandra; Manan, Saiful (Vocational School Diponegoro University, 2013)
Ruky Sandra Ary M, Saiful Manan, in this paper explain that parking lot which is widely used today do not present an empty parking location data, causing the vehicle entering the parking area must first find an empty parking space. This led to queues of vehicles becomes unavoidable. Even vehicles must berputarputar first to find an empty parking space. Therefore, it needs a parking system that can alert parking block capacity is still empty. Parking tariff determination system also plays an important role, most of the park determines the rate only on the type of vehicle rather than on how much time parking felt unjust for some people. This study designed a microcontroller-based parking system that can determine the number of cars remaining at the same time counting parking rates is a unified tool that can be divided into two, namely, hardware and software as a mechanical system that will work as a control system and the process of calculating tariffs. Keywords: parking system, Microcontroller 8535, Infrared, parking rates, Password